Kalajoen kahakka Viimeinen kansankapina 1953 - Saari, Juho (Historiallinen arkisto, 2022)
Nothing exceptional happened in front of the youth association building in Kalajoki on 9 September 1953. There was a minor confrontation between regional police forces and local youth, but hundreds of similar events happened in small municipalities across Finland. The event took about ten minutes, nobody was seriously hurt, and collective feelings quickly calmed down. However, after extensive investigations, the regional prosecutor thought otherwise and prosecuted half a dozen local men for rebellion against the state in January 1954. The district court agreed. The municipality was shocked, and the Finnish society was taken by surprise. The case ended up in Supreme Court. This book analyses why and how the last rebellion in the history of Finland occurred in a tiny municipality on the west coast of Finland. The analysis is based on historical microsociology that integrates the insights of microhistory and microsociology into event structure analysis and collective memory studies.